Cardiopulmonary bypass for advanced thoracic surgery - Wiebe, Karsten (Shanghai Chest; Vol 2 (January 2018): Shanghai Chest, 2018)
The review article by Fuentes-Gago et al. (1) describes in detail two cases of extended thoracic tumor resections with the help of cardio-pulmonary bypass. The authors nicely explain application and handling of the cardiopulmonary bypass.